Catastrophizing and pain-related fear predict failure to maintain treatment gains following participation in a pain rehabilitation program. (August 2016) - Moore, Emily; Thibault, Pascal; Adams, Heather; Sullivan, Michael J.L.
Abstract : Abstract: The present study explored whether pain-related psychosocial risk factors played a role in determining whether treatment gains were maintained following participation in a rehabilitation intervention for musculoskeletal injury. The study sample consisted of 310 individuals (163 women, 147 men) with work-related musculoskeletal conditions who were enrolled in a physical rehabilitation program. Measures of pain severity, pain catastrophizing and pain-related fear were completed at the time of admission and at the time of discharge. Pain severity was assessed again at 1-year postdischarge. Participants were classified as "recovered" if they showed a decrease in pain of at least 2 points and rated their pain at discharge as less than 4/10. Recovered participants were considered to have failed to maintain treatment gains if their pain ratings increased by at least 2 points from discharge assessment to 1-year follow-up, and they rated their pain as 4/10 or greater at 1-year follow-up. The results of a logistic regression revealed that participants with high posttreatment scores on measures of catastrophizing and fear of pain were at increased risk of failing to maintain treatment gains. The findings suggest that unless end-of-treatment scores on catastrophizing and fear of pain fall below the risk range, treatment-related reductions in pain severity may not be maintained in the long term. The clinical and theoretical implications of the findings are discussed.